2013
DOI: 10.1103/physrevlett.111.268302
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity-Based Mechanism for the Collective Motion of Self-Propelled Particles with Springlike Interactions: A Model System for Natural and Artificial Swarms

Abstract: We introduce an elasticity-based mechanism that drives active particles to self-organize by cascading self-propulsion energy towards lower-energy modes. We illustrate it on a simple model of self-propelled agents linked by linear springs that reach a collectively rotating or translating state without requiring aligning interactions. We develop an active elastic sheet theory, complementary to the prevailing active fluid theories, and find analytical stability conditions for the ordered state. Given its ubiquity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 37 publications
7
91
0
Order By: Relevance
“…By constantly converting external energy into directed motion, such systems of self-propelled particles can be driven into a non-equilibrium steady state. Steady dynamic states of orientationally ordered collective motion can arise [10][11][12][13][14][15][16][17][18][19], but also swirling and turbulent-like situations were observed [20][21][22][23]. There are different possibilities how to provide the energy input in experiments: light, if sufficiently strong, can create a temperature gradient leading to self-thermophoresis [24,25], or lead to the local demixing of a binary solvent [26].…”
Section: Introductionmentioning
confidence: 99%
“…By constantly converting external energy into directed motion, such systems of self-propelled particles can be driven into a non-equilibrium steady state. Steady dynamic states of orientationally ordered collective motion can arise [10][11][12][13][14][15][16][17][18][19], but also swirling and turbulent-like situations were observed [20][21][22][23]. There are different possibilities how to provide the energy input in experiments: light, if sufficiently strong, can create a temperature gradient leading to self-thermophoresis [24,25], or lead to the local demixing of a binary solvent [26].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, Hemelrijk & Hildenbrandt [196] used a detailed model of the motion rules of starlings and found that SF correlations were observed even when far from any Figure 5. A self-organized flocking process that starts in a disordered state (left) and eventually converges to a parallel motion state (adapted from Ferrante et al [195]). This system was shown to exhibit scale-free correlations due to the propagation of collective modes in the work by Huepe et al [194].…”
Section: Collective Mode Dynamicsmentioning
confidence: 99%
“…Huepe et al [194], for example, postulate this mechanism as the source of the SF correlations measured for speed fluctuations. They proposed a simple position-based model that describes an idealized active elastic system in which largescale collective oscillations (corresponding here to the low-mass modes) dominate the dynamics [195] (see figure 5 for an example of possible dynamics induced by this system). They then showed in numerical simulations that the presence of these collective oscillations of the fundamental elastic modes produces scale-invariant correlations of the angular and speed fluctuations in active systems.…”
Section: Collective Mode Dynamicsmentioning
confidence: 99%
“…Several researches have reported collective motions resulting from attraction-repulsion interaction without the alignment252627282930. For example, active Brownian agents that interact globally with each other by attraction show noise-induced transition between translational and rotational motions2526.…”
mentioning
confidence: 99%